2007
DOI: 10.1089/cap.2007.018
|View full text |Cite
|
Sign up to set email alerts
|

Acetyl-L-Carnitine (ALC) in Attention-Deficit/Hyperactivity Disorder: A Multi-Site, Placebo-Controlled Pilot Trial

Abstract: ALC appears safe, but with no effect on the overall ADHD population (especially combined type). It deserves further exploration for possible benefit specifically in the inattentive type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…It should be mentioned that we used ALC as adjunctive therapy in the present study. Nevertheless, the results of this trial are in agreement with a multi-site 16-week pilot randomized trial that showed ALC to be safe, but with no effect on the overall ADHD population (especially combined type) [9]. Although the present study yielded negative results, investigators see value in these reported findings for future cataloguing of this information.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It should be mentioned that we used ALC as adjunctive therapy in the present study. Nevertheless, the results of this trial are in agreement with a multi-site 16-week pilot randomized trial that showed ALC to be safe, but with no effect on the overall ADHD population (especially combined type) [9]. Although the present study yielded negative results, investigators see value in these reported findings for future cataloguing of this information.…”
Section: Discussionsupporting
confidence: 86%
“…Another study by Toriolli et al showed that ALC represents a safe alternative to the use of stimulant drugs for the treatment of ADHD in FXS children [8]. Nevertheless, a recent randomized and placebo controlled trial has reported that ALC is safe, but with no effect on the overall ADHD population [9]. We assessed the effects of ALC plus methylphenidate versus methylphenidate plus placebo in the treatment of children with attention deficit hyperactivity disorder.…”
Section: Introductionmentioning
confidence: 98%
“…Reviews on alternative treatments for ADHD (Arnold, 1999;Rucklidge, Johnstone, & Kaplan, 2009) indicate that the number of peer reviewed studies on such treatments is very limited in comparison to the hundreds on psychopharmacological approaches. Studies investigating one ingredient at a time have shown some promise (e.g., zinc/ zinc sulphate; Akhondzadeh, Mohammadi, & Khademi, 2004;Bilici et al, 2004); magnesium; Starobrat-Hermelin & Kozielec, 1997), other nutrients show mixed responses across studies (e.g., acetyl-l-carnitine; Arnold et al, 2007;Van Oudheusden & Scholte, 2002) and other individual nutrients simply have no support for their use in the treatment of ADHD (e.g., phenylalanine; Wood, Reimherr, & Wender, 1985;l-tyrosine;Nemzer, Arnold, Votolato, & McConnell, 1986;Reimherr, Wender, Wood, & Ward, 1987). However, this approach of using one ingredient at a time may be too simplistic, as interventions of single ingredients may actually upset nutritional balances, creating deficiencies in other nutrients (Mertz, 1994).…”
mentioning
confidence: 99%
“…Many theories have been proposed as to why nutrients might effect positive change on psychiatric symptoms, including correcting in-born errors of metabolism (Ames, Elson-Schwab & Silver 2002;Kaplan et al 2007), addressing dysfunction within the mitochondria (Parikh et al 2009), improving energy metabolism (Arnold et al 2007), and improving gut inflammation (Wärnberg et al 2009). In the drug addiction literature, studies are showing that providing the precursors to key neurotransmitters via amino acids can alleviate withdrawal symptoms (Chen et al 2012), suggesting that the administration of precursors of neurotransmitters leads to augmentation of those neurotransmitters responsible for symptom reduction.…”
Section: Discussionmentioning
confidence: 99%